PEMANFAATAN LIMBAH MEMBRAN CANGKANG TELUR MENJADI MATERIAL TEKSTIL - Antik Larasati; Morinta Rosandini (Universitas Pendidikan Indonesia, 2017)
The egg is a familiar thing to us. Eggs can be used for foods ingredients, beauty, and many things in our daily life. The study was backed by the lack of utilization of eggshells waste to increase the economic and aesthetic value, this is because until recently part of the eggshells are mainly part of the membrane is only considered garbage that is no longer useful. The purpose of this research is the processing waste membrane eggshells to become a textile material. This research uses qualitative research methods by doing research directly in the field. The research was conducted in two stages. First stage related to the separation part of the eggshell with eggshells membrane. Second stage was to research how to make eggshells membrane using as a new textile material. The results of the first stage research related to the discovery of the most effective ways of separating parts of the eggshells with the membrane of eggshells, the way is soaking eggshells in 25% concentration of vinegar. The results of the research second stages, founding a way how to make an eggshells membrane so it can be used as a new textile material. The most effective way is by the coating process with silicon oil, soaking with a solution of salt and soaking with softener clothes.